Participatory planning and management for effective and efficient irrigation system case study of Bago River Irrigation System, Bago City, Negros Occidental - Babiera, Nicanor O.; Lidasan, Hussein S. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
Improved rice production through effective and efficient irrigation services is the main strategy of the government for Food Staple Sufficiency Program (FSSP), as the overall focus of this study at the local level. The program aims for an average increase of 4% for rice production and harvest area of 2% annually. Specifically, on per hectare basis, the FSSP aims for the increase of yield on rice production from 4.16mt?ha in 2011 to 4.93 mt/ha in 2016. With this target, ensures the country's food security, food sufficiency and food sustainability.In the context of Bago River Irrigation System (BRIS) as study area, food security dimension of the FSSP is achieved and secured. Production is on increasing trend from 4.2mt/ha from 2010 to 4.5mt/ha in 2013. In terms of food sufficiency for the locality, the irrigation system stabilizes the supply and price of rice through continued production. Secured cropping patterns, five cropping for two (2) years and on time production are the off-shoot of effective planning with the implementation of cropping calendar and pattern of planting and provide equal opportunity of farmers to plant o time. Assured cropping and availment of irrigation water are attributed to the newly rehabilitated physical structures which are perceived by farmers to be both effective and efficient. The research is also focused on the factors that ensure effective and efficient operation and maintenance of the irrigation system with the Irrigation Management Transfer (IMT) program of NIA. There are four components in the management of irrigation system the operation and maintenance, organizational, financial and organizational discipline (implementation and sanction of policies/regulations). Statistical analysis showed that, Irrigation Service Fee (ISF) collection, irrigated area, and production are related to each other. Relationship between Operation and Management Aspects of the functionality of IA which are Organizational,Financial and Organizational Discipline Aspect proved that Organizational Discipline Aspect has a positive effect on the O&M Aspect.Under the NIA's mandate, ISF must be regularly collected from the beneficiaries as the agency's source of funds. However, under IMT program, ISF collection activities are delegated to the Irrigators Association (IA). Remuneration and incentives are given to the IA depending on their performance in ISF collection related activities and in the operation and maintenance. Date showed that IA could hardly collect ISF collection as indicated by incentives received by IAs having Model 2 Contract, Model 2 assumes all the responsibilities including ISF Collection and remittance and sharing of incentives is based on ISF collected with agreed sharing scheme. Under the NIA mandate ISF is considered alien to the land and one consideration is in this study is to incorporate ISF to land tax or other mechanisms with LGU as the lead agency in spatial planning and in local tax management.Existing mandates of LGUs provides for the need to integrate the plans and the operation and management activities of irrigation into a comprehensive multi-sectoral development plan. This multi-sectoral plan must be initiated by the development council and approved by its Sanguniang. The plan has the influence in setting the direction of economic and social development, and coordinating development efforts within its territorial jurisdiction.The study revealed many discussion points between the LGU and NIA in planning and managing irrigation system. Among these are the planning and management for irrigation roads, drainage canals, canal embankments as open space/parks and tourism areas. In the case of Bago RIS, the study area, planning is well a defined activity by the NIA and IA at Turn Out Service Area Group (TSAG) or at the field level, IA and NIA and Federation Levels. Data shows that planning sessions are done through meetings. However, participation and involvement by other stakeholders is very limited. With the implementation of IMT, there is no planning tool introduced to be used by IA leaders.Plans are still prepared using NIAs existing planning tool. Further NIA and IA plans are not well articulated and included in the Barangay Plans, Municipal/City plans and Provincial plans either in long range plan and annual plans. Irrigation system management by the IA in the study area, BRIS, is in consonance with IMT program of NIA. However, on the aspect of monitoring and evaluation, there is no tool introduced to capture the new roles and responsibilities on NIA and IA. Monitoring and evaluation are very important functions of management. NIA delegated its responsibilities on operation and maintenance to farmers however there is no accompanying monitoring and evaluation tool that are "farmer friendly" e.g. easy to understand and interpret considering the educational attainment of farmers-leaders. Survey results provide that of the 86 respondents, 52% or 45 of them are only high school graduate/reached high school level. Based on interviews, KIIs and FGDs, assessment, respondents shared that monitoring and assessment activities are only done during meetings and discussion and the results are reflected in minutes of meetings, no M&E tool specifically introduced for farmers-leaders for them to easily visualize the status of IMT plan implementation. The study consolidated the plans, accomplishment and performances of IAs and simulated the results using the AMOEBA Model and with the existing functionality survey indicators and parameters and indicators suggested under sustainability development indicators related to sustainability for agriculture as advocated by Saleth and Dinar (1999); Bell and Morse (1996); Swift (1994). The AMOEBA Model provides a graphic representation of the performance of the system and assessed over a certain number of aspects/qualities that cannot be expressed/captured by the existing monitoring and evaluation tool. As indicated in the study, at the local level, the presence of irrigation system within the LGU is beneficial. It is the source of food, provides access and mobility for rural community through (irrigation roads) and satisfies the spatial requirements of the populace through open space, protection area for production and eco-tourism among others.Data showed that irrigation management is related to policies and rules implemented. Under the present set up, IA promulgates irrigation related policies and regulations, but such policies cover only IA members and not the entire community. Local Government officials play vital role in assisting IAs improving the "organizational discipline aspect" (policies and regulations planning and implementation) of irrigation management. There is a need to integrate irrigation plans with that of Barangay Plans, programs and projects, adoption of IA Policies by Barangay Council to become Barangay Ordinance. Also there is a need for the inclusion of IA and NIA plans into the Comprehensive Land Use Plan (CLUP) of the city/municipality, inclusion of IA project into Medium Term Development Plans, Local Investment Plan. Further, there is a need for the legislation of the IA policies and regulations to be considered as Barangay Ordinance. The Barangay Ordinance could be endorsed to the City/Municipality for Municipality/City government to further provide wider impact of policies at Provincial Level in the form of provincial ordinance, provincial programs and projects annual targets and ultimately provincial budgets.The study provides as its major contribution to the existing knowledge of urban and regional planning a proposed framework for participatory planning and management for irrigation system. The framework integrates all parts of various stakeholders related to irrigation/agriculture into barangay, municipality and provincial plans. The LGUs (Barangay, Municipal, Provincial) under Sections 2c, 26 and 34 are mandated to ensure participation's of stakeholders in the planning, implementation and management of all development projects.
Vita.
Thesis (Ph.D. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Irrigation -- Philippines -- Bago City (Negros Occidental); Irrigation farming -- Philippines -- Bago City (Negros Occidental); Irrigation farming -- Economic aspects -- Philippines -- Bago City (Negros Occidental); Cropping systems -- Philippines -- Bago City (Negros Occidental); Rural development -- Philippines -- Bago City (Negros Occidental)